Teacher Strategies in Shaping Student Character in Science Learning at Class V - Yeni Erita; Yulia Septi Wahyuni; Delfi Eliza; Risda Amini (Postgraduate, University of Mataram, 2024)
This research aims to: describe the forms of student character at SDN 03 Sungai Angek, describe the character development carried out at SDN 03 Sungai Angek, describe the teacher's strategy in forming student character, describe the implementation teachers towards the principal's program about realizing good student character at SDN 03 Sungai Angek. The method used is a qualitative type, with research data collection obtained using the triangulation technique with documentation, interviews, and observation data collection techniques. The steps to analyze the data are by collecting data, reducing the data, and presenting the data. The results of this research show that the material for character development for students at SDN 03 Sungai Angek includes religious character development, disciplinary character development, and social character development. The formation of student character can be started from several methods, namely making daily worship reports, greeting parents before leaving for school, and applying smiles and greetings in society and the environment. The teacher's strategy in forming student character is through an integration strategy which includes: first, integrating character through daily activities in the form of providing examples such as warnings, advice, and routine activities.